Technical note: An analytical approach for (U–Th) ∕ He dating of goethite by sample encapsulation in quartz ampoules under vacuum, with an example from the Amerasian Basin, Arctic Ocean - O. V. Yakubovich; N. P. Konstantinova; M. O. Anosova; M. M. Podolskaya; E. V. Adamskaya (Geochronology, 2024)
We propose an analytical approach for (U–Th) / <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="e653eaf840568ee76bb20ba3bf368ae0"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-6-653-2024-ie00004.svg" width="8pt" height="14pt" src="gchron-6-653-2024-ie00004.png"/></svg:svg> He dating of Fe-(oxyhydr)oxides that includes sealing samples in quartz ampoules and demonstrates its suitability as a reliable tool for the investigation of geological processes. The (U–Th) / <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="57ee8123d9c9aefcf23d9c7f6463c158"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-6-653-2024-ie00005.svg" width="8pt" height="14pt" src="gchron-6-653-2024-ie00005.png"/></svg:svg> He ages of goethite clasts and veins from Fe- and Mn-oxide cemented rocks recovered from the slope of the Chukchi Borderland in the Amerasia Basin demonstrate reproducibility, yielding a weighted mean age of 8.6 ± 0.3 Ma ( n =4 ) and 4.8 ± 0.4 Ma ( n =2 ), respectively, providing insights into the Neogene mineralization history of the region. This study also focuses on the sample preparation technique, which might influence the (U–Th) / <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="880d1b22cfae9b4167ff115d05c6894c"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-6-653-2024-ie00006.svg" width="8pt" height="14pt" src="gchron-6-653-2024-ie00006.png"/></svg:svg> He ages. Our data indicate that some of U can be leached from the goethite during sonication by distilled water, which might result in erroneous (U–Th) / <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="3af55808dad7e355d8e0b0b2a0272ce7"><svg:image ...